Customer food preferences to be served on Lasalle Diners-LSU-Ozamiz City - Tapitan, Maritess M. (2009)
This paper sought to find out the food preferences of the customers in La Salle Diners-LSU, Ozamiz City. A descriptive deign was used to collect data through the use of survey questionnaire. It included all the customers in La Salle Diners both students and teachers (male and female), during the 2nd semester 2008-2009.
This will serve as the basis for the cook (personnel) in La Salle Diners on what foods to prepare for their customers.
Keywords: Food preferences